INTEGRATION OF BIOMARKERS INTO THE PRACTICE OF TREATING PATIENTS WITH HEART FAILURE: THE ROLE OF DETERMINING THE BLOOD LEVEL OF NATRIURETIC PEPTIDES - S. R. Gilyarevskiy; M. V. Golshmid; I. M. Kuzmina (Рациональная фармакотерапия в кардиологии, 2017)
A clinical role of biomarkers (especially, natriuretic peptides) is discussed in the article. The most important evidences of clinical effectiveness of using biomarkers in patients with suspected heart failure and in patients with confirmed diagnose of heart failure are reviewed. The need to use natriuretic peptides in patients with takotsubo syndrome is discussed. Limited diagnostic value of using natriuretic peptides in renal dysfunction, as well as in other diseases in which the concentration of natriuretic peptides may increase in the absence of heart failure, is also discussed.